2008
DOI: 10.1007/s10799-008-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Do online reviews affect product sales? The role of reviewer characteristics and temporal effects

Abstract: Online product reviews provided by consumers who previously purchased products have become a major information source for consumers and marketers regarding product quality. This study extends previous research by conducting a more compelling test of the effect of online reviews on sales. In particular, we consider both quantitative and qualitative aspects of online reviews, such as reviewer quality, reviewer exposure, product coverage, and temporal effects. Using transaction cost economics and uncertainty redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(147 citation statements)
references
References 33 publications
2
120
0
Order By: Relevance
“…Based on the results of Table 2 we may confirm two hypotheses of the survey and conclude that product quality may influence positively on attitudinal as well as behavioral loyalty, positively. The results of this study are consistent with other findings reported by Romaniuk and Nenycz-Thiel (2013), Hu et al (2008) and Lee and Shin (2014). In other words, an increase on product quality has to increase attitudinal loyalty much more than behavioral loyalty does.…”
Section: Results and Conclusionsupporting
confidence: 93%
“…Based on the results of Table 2 we may confirm two hypotheses of the survey and conclude that product quality may influence positively on attitudinal as well as behavioral loyalty, positively. The results of this study are consistent with other findings reported by Romaniuk and Nenycz-Thiel (2013), Hu et al (2008) and Lee and Shin (2014). In other words, an increase on product quality has to increase attitudinal loyalty much more than behavioral loyalty does.…”
Section: Results and Conclusionsupporting
confidence: 93%
“…Specifically, peripheral cues (i.e., star ratings and rankings of the reviews) are useful in the information search stage whereas central information processing (i.e., the number of total words in a review and the number of negative words) is influential in the stage of the evaluation of alternatives. Hu, Liu, and Zhang (2008) concluded that online consumer reviews infer product quality and reduce product uncertainty, in turn aiding the final purchase decision.…”
Section: Online Consumer Reviewsmentioning
confidence: 99%
“…The rationale for such access is that review information of this kind has been shown to play a valuable role when it comes to helping users to make purchasing decisions, increasing the conversion rate of casual browsers into informed, satisfied buyers. For example, Hu et al [10] describe the results of one study on the value of online reviews, concluding that consumers do understand the value di↵erence between favourable and unfavourable opinions and respond accordingly. Furthermore, when consumers read online reviews, they pay attention not only to review scores, but to other contextual information such as a reviewer's reputation and reviewer exposure.…”
Section: Introductionmentioning
confidence: 99%